Bis-imidazolium functionalized self-crosslinking block polynorbornene anion exchange membrane. (28th April 2020) - Zhang, Feng; He, Xiaohui; Cheng, Changwen; Huang, Shengmei; Duan, Yapeng; Zhu, Chuanyi; Guo, Yan; Wang, Kai; Chen, Defu
Abstract: Anion exchange membranes (AEMs) are widely studied as an important component of fuel cells. In this paper, series self-crosslinking AEMs are obtained by copolymerization of the prepared bis-imidazolium functionalized ionic liquids. The block copolymer shows excellent thermal stability with a decomposition temperature (Td) of 300 °C. And the mechanical properties of AEMs in OH − are significantly improved due to the crosslinking of epoxy groups. The transmission electron microscopy (TEM) test results show a good microscopic phase separation structure and form ion channels in the membranes, which is benefited to ions conductivity. The OH − conductivity of AEMs is measured as above 24 10 − 3 S cm − 1 and 95 10 − 3 S cm − 1 at 30 °C and 80 °C, respectively. In addition, the AEMs also exhibits excellent swelling performance, the highest is only 20.86% at 80 °C. And the conductivity of all AEMs remained above 90% after being immersed in 1 M NaOH aqueous at 60 °C for 250 h. The peak power density of the AEMs reaches 207.95 mW cm −2 at current density of 403 mA cm −2 . Highlights: A kind of bis-imidazolium functionalized norbornene ionic liquid was synthesized. The resulting membranes exhibit excellent anti-swelling and mechanical properties. The resulting membranes exhibit high ionic conductivity and peak power density.